Socio-Economic Growth and Development Through Innovation on The Example of Tourism Companies in Poland - Małgorzata BROJAK-TRZASKOWSKA (Communications of International Proceedings, 2020)
The main objective of the research is to identify exogenous conditions for growth and development through innovation in the economy on the example of Polish tourism companies and to define a general course of action for improvement in the scope covered by the research. The rationale for research is regarding growth and economic development as an up‑to-date and important issue. The research process involved the method of critical analysis of the source literature, especially in the theoretical part. The empirical part was based on the analysis of the research material obtained by means of a survey and the observation method, while the application part uses mainly logical reasoning and the synthesis method. The article presents results of the surveys conducted in tourism companies regarding the external determinants of innovative growth and development, in terms of macroeconomic, formal, legal, institutional and socio-cultural aspects. The study was conducted twice at an interval of five years. The results of the surveys indicate that in the case of the first survey, the formal and legal factors prevailed in the structure of external determinants of growth and development of tourism companies, while in the second survey – macroeconomic factors.
Keywords: Macro- and Microeconomic Growth and Development; Tourism; Innovations; Tourism Company.